State parliaments’ departure from the practice of standing orders: The evolution of Australian parliamentary practice - Porter, Jennifer (Routledge, 2014)
This article analyses the extent to which contemporary Australian state parliaments observe the procedures and practices of the British House of Commons and the potential reasons for departures from those procedures. It considers a recent example of significant divergence from House of Commons practice. In Western Australia’s state parliament, the speaker exercised the casting vote on a motion of closure (a ‘gag’ motion). The article examines this procedural divergence for possible insights into the nature of, and reasons for, Australian departures from House of Commons practice.